1980
DOI: 10.1007/bf01915807
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of modified faujasites

Abstract: A derivatograph was used to follow the modification of the skeleton structure and thermal stability of zeolites in sodium and ammonium forms. Analogous investigations were carried out by independent methods such as IR and X-ray. Comparison showed good agreement between the results. The controlled dealumination of the Y-type zeolite enhanced the thermal stability.Modified zeolites prepared by treatment with ethylene diamine tetraacetic acid (H4 EDTA) and subsequent activation profoundly alter their structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
12

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
5
0
12
Order By: Relevance
“…For the samples analyzed, this peak occurred at 720 °C for the deactivated catalyst and at 715 °C for the remediated catalyst. According to Chandwadkar and Kulkarni (1980), lower dehydration temperatures are expected for zeolites with higher Si/Al ratios, as occurred with the remediated catalyst. It was also found that, for the remediated catalyst, the second endothermic peak showed a higher amplitude, or greater absorption of energy during the phase transition, indicating a greater presence in the material of hydroxyl groups.…”
Section: Damage Assessment On the Catalyst Structurementioning
confidence: 99%
“…For the samples analyzed, this peak occurred at 720 °C for the deactivated catalyst and at 715 °C for the remediated catalyst. According to Chandwadkar and Kulkarni (1980), lower dehydration temperatures are expected for zeolites with higher Si/Al ratios, as occurred with the remediated catalyst. It was also found that, for the remediated catalyst, the second endothermic peak showed a higher amplitude, or greater absorption of energy during the phase transition, indicating a greater presence in the material of hydroxyl groups.…”
Section: Damage Assessment On the Catalyst Structurementioning
confidence: 99%
“…Los resultados revelaron que la aplicación de tratamientos de molienda tradicional en sistemas de molino de bolas no contribuye a la mejora de la dispersión de las partículas de humo de sílice a través de la destrucción de los aglomerados. El tratamiento tiene un efecto importante durante los primeros minutos de molienda, donde los aglomerados de mayor tamaño son destruidos como consecuencia del impacto entre las partículas y los cuerpos moledores, sin embargo a tiempos más prolongados no se observó una mejora en el grado de dispersión, donde el tamaño medio de partícula fue superior a 20 µm y un contenido de partículas sub-micrométricas inferior al 1% [55].La aplicación de tratamientos de ultrasonidos en humo de sílice es evaluada inicialmente por Chu et al [56], el cual estudió el grado de dispersión de la partículas en una suspensión acuosa con diferentes valores de pH. Haïder et al [57] evaluó la utilización de ultrasonidos para la disgregación de aglomerados de humo de sílice y su efecto en la…”
unclassified
“…Materiales con menores distribuciones de tamaño de partícula exhiben una mayor superficie específica y por tanto un mayor grado de reactividad. Estos resultados son coherentes con Wolsifer [61] quien resalta la mejora en el grado de dispersión y reactividad del humo de sílice después de ser sometido a un tratamiento de ultrasonidos.Por otra parte la destrucción de los aglomerados tiene un efecto positivo sobre la reología de las pastas, otorgándole una mayor fluidez y la posibilidad de utilizar menores relaciones agua/conglomerante y menores contenidos de aditivo [55]. Este efecto también ha sido encontrado recientemente por otros investigadores [62, 63].…”
unclassified
See 2 more Smart Citations